2020
DOI: 10.1101/2020.05.05.079749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneous activity changes in large-scale cortical networks in older adults couple to distinct hemodynamic morphology

Abstract: Neurovascular coupling is a dynamic core mechanism supporting brain energy demand. Therefore, even spontaneous changes in neural activity not linked directly to goal-directed behavior are expected to evoke a vascular hemodynamic response (HDR). Here, we developed a novel procedure for estimating transient neural activity states based on source-localized electroencephalogram (EEG) in combination with HDR estimation based on simultaneously acquired functional magnetic resonance imaging (fMRI). We demonstrate a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 189 publications
(302 reference statements)
0
11
0
Order By: Relevance
“…Each RSN state can be described by its distinct spectral power and phase-locking profile; these profiles are summarized by averaging over frequency bands in Figure 2B for RSN states 1-4. This highlights that RSN state 1 was associated with activity over the parietal cortex; the equivalent network in simultaneous electroencephalogram (EEG)-fMRI studies has been shown to be anticorrelated with the dorsal attention network (DAN) (Mantini et al, 2007;Sitnikova et al, 2020); thus, activation of RSN state 1 corresponds to the DAN switching off. RSN state 2 combines high-power signals in frontal and temporal regions with coherent oscillations in the lateral parietal cortex, regions that comprise the DMN.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 92%
See 1 more Smart Citation
“…Each RSN state can be described by its distinct spectral power and phase-locking profile; these profiles are summarized by averaging over frequency bands in Figure 2B for RSN states 1-4. This highlights that RSN state 1 was associated with activity over the parietal cortex; the equivalent network in simultaneous electroencephalogram (EEG)-fMRI studies has been shown to be anticorrelated with the dorsal attention network (DAN) (Mantini et al, 2007;Sitnikova et al, 2020); thus, activation of RSN state 1 corresponds to the DAN switching off. RSN state 2 combines high-power signals in frontal and temporal regions with coherent oscillations in the lateral parietal cortex, regions that comprise the DMN.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 92%
“…Activity in the gamma band (>30 Hz) has consistently shown a strong correlation with a subsequent BOLD signal (Niessing et al, 2005;Nir et al, 2007); however, a more complex relationship emerges between the BOLD signal and activity in lower-frequency bands, in which electrophysiological RSNs are largely defined (Brookes et al, 2011;Mantini et al, 2007). It has now been shown that different RSN states show markedly different hemodynamic profiles; in particular, the DMN and DAN evoke BOLD signals that are opposed in polarity and distinct in their temporal decay profile (Sitnikova et al, 2020). If the DMN state visits cluster together in time while being linked to high-frequency power increases, as our results indicate, then this may explain these distinct profiles and provide a key bridge between the understanding of RSNs recorded across distinct modalities.…”
Section: Articlementioning
confidence: 99%
“…To the best of our knowledge, a microstate analysis of MEG data has not yet been developed. The HMM approach has been applied to EEG power envelopes (Hunyadi et al, 2019; Sitnikova et al, 2020), but the focus was on the relationship with fMRI networks rather than MEG or EEG microstates. Here, we assessed the impact of both the state clustering model and the recording modality on temporal and spatial signatures of transient brain states.…”
Section: Introductionmentioning
confidence: 99%
“…2B for RSN-states 1-4. This highlights that RSN-state 1 was associated with activity over parietal cortex; the equivalent network in simultaneous EEG-fMRI studies has been shown to be anticorrelated with the Dorsal Attention Network (DAN) (20,21); thus the activation of RSN-state 1 corresponds to the DAN switching off. RSN-state 2 combines high power signals in frontal and temporal regions with coherent oscillations in lateral parietal cortex, regions that comprise the DMN.…”
Section: Spontaneous Replay Coincides With Activation Of the Default mentioning
confidence: 89%
“…Activity in the gamma band (>30Hz) has consistently shown a strong correlation with a subsequent BOLD signal (39,40), however a more complex relationship emerges between the BOLD signal and activity in lower frequency bands, in which electrophysiological RSNs are largely defined (10,20). It has now been shown that different RSN-states show markedly different hemodynamic profiles; in particular, the DMN and DAN evoke BOLD signals that are both opposed in polarity and distinct in their temporal decay profile (21). But if the DMN state visits cluster together in time whilst being linked to high frequency power increases, as our results indicate, then this may help to explain these distinct profiles and provide a key bridge between the understanding of RSNs recorded across distinct modalities.…”
Section: Discussionmentioning
confidence: 99%